Pharmacological Characterization of a Novel ENaCα siRNA (GSK2225745) With Potential for the Treatment of Cystic Fibrosis. - Clark, K; Hughes, SA; Bulsara, P; Coates, J; Moores, K; Parry, J; Carr, M; Mayer, R; Wilson, P; Gruenloh, C; Levin, D; Darton, J; et al. (2013)
Lung pathology in cystic fibrosis is linked to dehydration of the airways epithelial surface which in part results from inappropriately raised sodium reabsorption through the epithelial sodium channel (ENaC). To identify a small-interfering RNA (siRNA) which selectively inhibits ENaC expression, chemically modified 21-mer siRNAs targeting human ENaCα were designed and screened. GSK2225745, was identified as a potent inhibitor of ENaCα mRNA (EC(50) (half maximal effective concentration) = 0.4 nmol/l, maximum knockdown = 85%) and protein levels in A549 cells. Engagement of the RNA interference (RNAi) pathway was confirmed using 5' RACE. Further profiling was carried out in therapeutically relevant human primary cells. In bronchial epithelial cells, GSK2225745 elicited potent suppression of ENaCα mRNA (EC(50) = 1.6 nmol/l, maximum knockdown = 82%). In human nasal epithelial cells, GSK2225745 also produced potent and long-lasting (≥72 hours) suppression of ENaCα mRNA levels which was associated with significant inhibition of ENaC function (69% inhibition of amiloride-sensitive current in cells treated with GSK2225745 at 10 nmol/l). GSK2225745 showed no evidence for potential to stimulate toll-like receptor (TLR)3, 7 or 8. In vivo, topical delivery of GSK2225745 in a lipid nanoparticle formulation to the airways of mice resulted in significant inhibition of the expression of ENaCα in the lungs. In conclusion, GSK2225745 is a potent inhibitor of ENaCα expression and warrants further evaluation as a potential novel inhaled therapeutic for cystic fibrosis.Molecular Therapy - Nucleic Acids (2013) 2, e65; doi:10.1038/mtna.2012.57; published online 15 January 2013.